2012
DOI: 10.1016/j.physa.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer adsorption by Monte Carlo simulation

Abstract: Elsevier Molina Mateo, J.; Salmerón Sánchez, M.; Monleón Pradas, M.; Torregrosa Cabanilles, C. (2012). Multilayer adsorption by Monte Carlo simulation. Physica A Statistical Mechanics and its Applications. 391(20):4474-4782. Abstract Adsorption phenomena are characterized by models that include free parameters trying to reproduce experimental results. In order to understand the relationship between the model parameters and the material properties, the adsorption of small molecules on a crystalline plane surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The bond fluctuation method , with explicit solvent is used to model self-assembled bilayers of lipids and their interactions with nanoparticles. This is a well-established and widely used theoretical method used to simulate various polymer systems ,, and lipid bilayers. ,,, BFM can be used to reproduce equilibrium and elastic properties of dense polymer systems, polymer solutions, networks, copolymers, and dendrimers. Essential properties of lipids such as membrane fusion and pore nucleation have also been studied and reproduced by previous studies with the BFM method.…”
Section: Methodsmentioning
confidence: 99%
“…The bond fluctuation method , with explicit solvent is used to model self-assembled bilayers of lipids and their interactions with nanoparticles. This is a well-established and widely used theoretical method used to simulate various polymer systems ,, and lipid bilayers. ,,, BFM can be used to reproduce equilibrium and elastic properties of dense polymer systems, polymer solutions, networks, copolymers, and dendrimers. Essential properties of lipids such as membrane fusion and pore nucleation have also been studied and reproduced by previous studies with the BFM method.…”
Section: Methodsmentioning
confidence: 99%
“…The bond fluctuation method , with explicit solvent is used to model self-assembled bilayers of lipids and their interactions with nanoparticles. This is a well-established and widely used theoretical method used to simulate various polymer systems and lipid bilayers. ,,, It was shown that the BFM accurately reproduces proper dynamical behavior of dense polymer systems, polymer solutions, networks, copolymers, and dendrimers. Muller et al . , have shown that the BFM model can reproduce essential properties of lipid bilayers and can address essential properties such as membrane fusion and pore nucleation.…”
Section: Methodsmentioning
confidence: 99%